Questioning Strategies Used by Debate Hosts in Mata Najwa and Kick Andy - Harahap, Fathul Jannah Harahap; Saragih, Erikson; Parasian, Nehemia Anugrah (Journal of English Education and Linguistics, 2025)
This research aimed to identify the questioning strategies used by debate hosts in Mata Najwa and Kick Andy and to investigate how these strategies influenced the flow of dialogue, issue framing, and the quality of informants’ responses. This research used a descriptive qualitative method. The results showed that Najwa Shihab employed five types of questions, namely opening questions, informative questions, Socratic questions, controlling questions, and rhetorical questions. These question types were used to build rapport, obtain factual explanations, stimulate critical thinking, ensure clarity, and provide subtle critique. Andy F. Noya employed six types of questions, consisting of opening questions, informative questions, Socratic questions, directing questions, alternative questions, and closing questions. These strategies functioned to guide the discussion, clarify political positions, and maintain structured and balanced interactions. The findings indicated that both hosts effectively managed the direction and focus of the conversation, prevented digression from key topics, and enhanced audience understanding of complex legal and political issues. The implications of this research indicated that people could apply effective questioning in daily life to understand complex information and evaluate issues critically. This research contributes to discourse analysis by highlighting the role of questioning strategies in public and political debates, while offering practical insights for hosts, journalists, and educators to guide discussions.